Monocationic cinchoninium catalyzed asymmetric oxohydroxylation of enoates - Li, Shuangqing (2022)
Asymmetric dihydroxylation and epoxidation are well-developed and widely used approaches to introduce chiral oxygenated functional groups with an alkene substrate. However, oxohydroxylation of an alkene, furnishing adjacent oxo and hydroxy groups, is less explored. In this paper, asymmetric oxohydroxylation of α-alkyl enoates with potassium permanganate catalyzed by monocationic quaternary ammonium salts derived from cinchona alkaloid is reported. A series of α-hydroxy-β-keto esters were obtained in up to 96% yield and 98% ee under user-friendly conditions. Synthetic application of oxohydroxylation was demonstrated in the synthesis of key chiral building blocks for thapsigargin and camptothecin synthesis. Control experiments indicated that, compared with tetrabutylammonium, monocationic chiral cinchoninium has a dramatic rate acceleration effect on catalytic permanganate oxidation.